ACADEMIC LEADERSHIP: A MISSING LINK IN HIGHER EDUCATION GOVERNANCE IN TIMES OF CHANGE? - Sagintayeva, A. (My University, 2014)
"Thus far, based on the brief data analysis of interviews among university leaders, the paper argues that the transition towards the development of academic leadership is a complex context-sensitive process. In the next decade or so, academic institutions will have to develop capacities to lead changes on their own campuses and develop their roles beyond the followship of externally designed initiatives. Both the state and the higher education leadership are likely to understand that change does not happen on its own but needs to be led by professionals and effective leaders both within and beyond universities" - ...
Keywords: academic leadership; higher education, Kazakhstan; academic leadership; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education